THE ANALYSIS OF ICT-BASED MEDIA ON EFL AND STUDENTS’ PERCEPTION OF THE MEDIA USED BY THE TEACHER AT SMA DWIJENDRA DENPASAR IN ACADEMIC YEAR 2021/2022 - Gusti Ayu Desiari; I Putu Yudi Sudarmawan (Widyasrama, 2022)
This research aims to find out what kinds of ICT-based media used to teach English at SMA Dwijendra Denpasar and how is the students’ perceptions of the media used by the teacher. This research used mixed methods to achieve the objectives of this study. The data will be presented in qualitative form supported by quantitative data in detailed calculations. There were two types of data collection techniques; interviews and questionnaires. The source of the data was taken from one of English teachers and thirty-one students of IPA1 at SMA Dwijendra Denpasar. The result of this research revealed that the teacher used various ICT-based media in devices and applications that are widely available in supporting the online learning process. The application used by the teacher are WhatsApp, Google form, Google Meet, and Email. Meanwhile, the results of the questionnaire show that students' perceptions of the media used by teachers are very effective to improve students' learning competency and are able to reach learning resources in a wider scope. Therefore, it is concluded that the student's response is a positive perception. The suggestions from researchers to English teachers are to improve display media used to get better student focus and always innovate. Meanwhile, for the students, they are expected to be able to form better habits that can help improving their competencies and focus to achieve learning objectives.